Light Microscopic Studies of Caecal Tonsil in Chicken (Gallus domesticus) - Kannan, T A; Ramesh, Geetha; Ushakumary, S; Raj, G Dhinakar; Vairamuthu, S (Indian Journal of Veterinary Anatomy, 2012)
Light microscopic studies on caecal tonsil of layer chicken revealed two types of lymphoid aggregations (germinal centre). The first type had an incomplete capsule and the second type was found encapsulated with connective tissue. The capsule of the germinal centre was consisted of many layers of flattened reticular cells. The germinal centre was consisted of lymphoblasts, lymphocytes of various sizes, reticular cells, plasma cells, mast cells and macrophages. The lymphocytic population was comparatively reduced with an increased number of fibroblasts and collagen fibres in 40 weeks-old birds. The caecal tonsil also had M cells with short and irregular microvilli.